Determining the Best Answers for Balinese Language Problems using Latent Semantic Analysis - Made Agus Putra Subali; I Ketut Putu Suniantara (Paradigma, 2022)
In Balinese, descriptions or essays are formed in an interrogative format using question words such as “akuda”, “apa”, “dija”, “kenken”, “kuda”, dan “nyen”. The assessment process on description questions tends to be more difficult and complex than multiple choice questions, this is because the description questions are described in sentence form. The solution to facilitate the assessment process on description questions can be done using automated essay scoring. Based on the results of previous studies, the Latent Semantic Analysis (LSA) method provides a better level of accuracy, because the LSA method uses the Singular Value Decomposition (SVD) method to obtain a new pattern of relationships between terms and reference terms. The data used in this study are five questions and their answer keys and there are five candidate answers for each question in Balinese. Based on the tests that have been carried out, the method used obtained an overall average accuracy of 70.26%, this shows that the LSA method can be used well in the assessment process or automatic essay assessment.